Experience of Cardiovascular Care Unit (CVCU) Nurses in Implementing Person Centered Care - Angraini, Silfi; Dewi, Wan Nishfa; Woferst, Rismadefi (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2025)
Background: Nurses in the Cardiovascular Care Unit (CVCU) have a key role in delivering Person Centered Care (PCC), which focuses on respecting patient preferences and improving care quality. Despite its importance, the implementation of PCC still faces several challenges in clinical practice. Objective: This study aimed to explore the experiences of CVCU nurses in implementing Person Centered Care in a hospital setting. Method: A qualitative research design with a phenomenological approach was used. Six nurses working in the CVCU were selected through purposive sampling. Data were collected using semi-structured interviews and analyzed through thematic analysis based on Colaizzi’s method. Results: The study identified five main themes: (1) Satisfaction with nursing care, (2) Involvement of patients and families, (3) Communication and collaboration between nurses and doctors, (4) Suboptimal communication patterns between nurses and patients, and (5) Time management and workload. Discussion: The findings indicate that PCC contributes to greater satisfaction in nursing care delivery. However, several barriers, such as limited communication and workload issues, need to be addressed. These insights can inform strategies for broader PCC implementation across different hospital wards. Hospital management should support this process by addressing potential obstacles and facilitating a supportive environment for PCC.